PENGARUH TERM OF PAYMENT, COMPLING HANDLING DAN E-WOM TERHADAP CUSTOMER LOYALTY - Ufi Rumefi (Jurnal Transparan Institut Teknologi dan Bisnis Yadika, 2021)
This study aims to find out and explain the simultaneous and partial influence of dependent variables: term of payment (TOP), compling handling (CH) and electric word of mouth (E-WOM) on independent customer loyalty (CR) variables.The method in this research is descriptive quantitative method by spreading questionnaire and conducted test with spss.16 test tool so that it will be able to get accurate data to be used as a research.The results of this study showed that the variable term of payment, compling handling and Electric word of mouth simultaneously affect the independence variable of customer royalty with a value of sig 0.001 < 0.005, while partially the term of payment variable affects customer loyalty with sig value, 0.002 < 0.005, as well as the compling handling variable affects customer royalty significantly with a t value of 0.025 < 0.05, electric word of mouth variables in a pasrisl does not affect customer loyalty variables with a sig value of 0.391 > 0.05.